2011
DOI: 10.1093/molbev/msr303
|View full text |Cite
|
Sign up to set email alerts
|

Low Evolutionary Diversification in a Widespread and Abundant Uncultured Protist (MAST-4)

Abstract: Recent culture-independent studies of marine planktonic protists have unveiled a large diversity at all phylogenetic scales and the existence of novel groups. MAST-4 represents one of these novel uncultured lineages, and it is composed of small (~2 μm) bacterivorous eukaryotes that are widely distributed in marine systems. MAST-4 accounts for a significant fraction of the marine heterotrophic flagellates at the global level, playing key roles in the marine ecological network. In this study, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 84 publications
1
33
0
Order By: Relevance
“…In a previous study, we showed that MAST-4 was composed of five main clades (Rodríguez-Martínez et al, 2012). To verify the robustness of these clades, we obtained 228 additional sequences of 500-650 bp encompassing the V9 region of the 18S rDNA and the ITS1 region from five different locations (Figure 1), including the locations from the previous study and one additional site.…”
Section: Validation Of the Different Mast-4 Cladesmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we showed that MAST-4 was composed of five main clades (Rodríguez-Martínez et al, 2012). To verify the robustness of these clades, we obtained 228 additional sequences of 500-650 bp encompassing the V9 region of the 18S rDNA and the ITS1 region from five different locations (Figure 1), including the locations from the previous study and one additional site.…”
Section: Validation Of the Different Mast-4 Cladesmentioning
confidence: 99%
“…It had 42 mismatches (except for one sequence with one mismatch and three sequences with two mismatches) to non-target sequences from the SILVA database (Pruesse et al, 2007). The reverse primer M4.58S-R (5 0 -GTTGCGAGAACCTA-GAC-3 0 ), located in the 5.8S rDNA, was designed to have a perfect match with the 22 MAST-4 sequences (Rodríguez-Martínez et al, 2012). This primer had at least two mismatches with all stramenopile sequences extracted from GenBank, except for some Labyrinthulida sequences (3 with no mismatches and 62 with one mismatch).…”
Section: Design Of Pcr Primersmentioning
confidence: 99%
See 3 more Smart Citations